MORPHO-ANATOMICAL PROFILE OF ELAEOCARPUS TUBERCULATUS ROXB - JAYASHREE, INDHIRAMUTHU; DH, GEETHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The anatomical studies of Elaeocarpus tuberculatus Roxb. (Elaeocarpaceae), an indigenous medicinal plant in the Indian pharmacopoeia. Methods: Fresh leaf and stem samples of E. tuberculatus were scrutinized macroscopic and microscopically by standard procedures. Results: Macroscopically, the leaves are simple, long, coriaceous, and rusty below, base obtuse, margin serrate, apex obtuse and petiole 3 cm long. Microscopically, the leaf showed the presence of four prominent collateral bundles. Paracytic stomata were distributed in the abaxial epidermis whereas the adaxial epidermis was apostomatic. The petiole was four-angled including wing bundles. The stem exhibited fissured periderm, wide secondary phloem, secondary xylem with incipient growth ring and abundant calcium oxalate crystals. Powdered microscopic study of the leaf revealed the presence of long whip-like epidermal trichomes, crystals, vessel elements showing pits and fiber-like sclereids. The stem powder showed thick-walled fibers with wide lumen, narrow fibers and a sclerenchyma cell showing wide pits. Conclusion: The results of the study can serve as a valuable source of information and provide suitable standards for the identification of E. tuberculatus in future investigations and applications